Psychological Characteristics of Volunteers - Bulatevych, Nataliya; Batrakina, Ielyzaveta (Psychological Prospects Journal, 2019)
The article analyzes psychological featers of volunteers and motivational factors of volunteer activity. Based on the analysis of the degree of affiliation and the need to maintain and establish contacts with others in the group of respondents involved in volunteering and the group of respondents who did not participate in volunteer work, it has been established that volunteers have a higher affiliation level than a group of people that not involved in volunteering. The study of the level of subjective control and personal responsibility of a group of volunteers and groups not involved in volunteering, showed that volunteers have a higher score on the scales of general internality, which is evidence of a high level of sense of subjective control over life events; on the scale of interpersonal relations, which are indicators of a higher level of sense of control of informal and formal relations with others, the ability to control the respect and sympathy of others; on the scale of failure, which means the perception of subjects of unpleasant events as a result of their own actions. It`s been shown that volunteers have a higher level of sense of social acceptability and social approval of their own life. On the basis of the diagnostics of socio-psychological attitudes of the two groups of respondents in the area of the motivational needs, it was established that the people involved in volunteering activity have dominating altruistic values, high indicators in the orientations on the process, as well as on freedom (independence, resistance to restrictions).
Keywords: volunteers; volunteer activity; motivation; values; social attitudes; affiliation